News from the Field: Has Another Lost Ark Been Found? - Yeivin, Zeʾev (The Biblical archaeology review, 1983)
I am pleased to inaugurate BAR’s "News from the Field" department with the first English publication of a most unusual find. It was recently discovered in the ancient city of Chorazim which overlooks the Sea of Galilee. The find is an almost unique pilaster whose function I will dare to suggest at the end […]